New report on the invasive Bondar's Nesting Whitefly (Paraleyrodes bondari Peracchi) on oil palm in India - Rao, N. B. V. Chalapathi; Ramani, B. S.; Bhagvan, B. V. K.; Sabana, A. A.; Rajesh, M. K. (Journal of Plantation Crops, 2023)
This communication is the new report of the neotropical invasive Bondar's Nesting Whitefly (BNW) , Paraleyrodes bondari Peracchi (Hemiptera: Aleyrodidae)incidence in oil palm in India. A typical feature of BNW infestation is the presence of woolly wax nests on the abaxial surface of oil palm leaflets. The nesting whitefly population was observed to increase phenomenally on oil palm and within a year ie., from 2021 to 2022, a 100 per cent palm infestation was observed. During this period the intensity per palm increased by 24.49 per cent and per leaf increased by 63.28 per cent. Analysis of the partial mitochondrial cytochrome oxidase subunit 1 (CO1) sequences from adult specimens indicated 100% nucleotide identity with Bondar's Nesting Whitefly from coconut.